Homologous recombination deficiency is inversely correlated with microsatellite instability and identifies immunologically cold tumors in most cancer types. (5th April 2022) - Budczies, Jan; Kluck, Klaus; Beck, Susanne; Ourailidis, Iordanis; Allgäuer, Michael; Menzel, Michael; Kazdal, Daniel; Perkhofer, Lukas; Kleger, Alexander; Schirmacher, Peter; Seufferlein, Thomas; Stenzinger, Albrecht
Abstract: Homologous recombination deficiency (HRD) leads to DNA double‐strand breaks and can be exploited by the use of poly (ADP‐ribose) polymerase (PARP) inhibitors to induce synthetic lethality. Extending the original therapeutic concept, the role of HRD is currently being investigated in clinical trials testing immune checkpoint blockers alone or in combination with PARP inhibitors, but the relationship between HRD and immune cell context in cancer is incompletely understood. We analyzed the association between immune cell composition, gene expression, and HRD in 9, 041 tumors of 32 solid cancer types from The Cancer Genome Atlas (TCGA). The numbers of genomic scars were quantified by the HRD sum score (HRDsum) including loss of heterozygosity, large‐scale state transitions, and telomeric allelic imbalance. The T‐cell inflamed gene expression profile correlated weakly, but significantly positively, with HRDsum across cancer types ( ρ = 0.17). Within individual cancer types, a significantly positive correlation was observed only in breast cancer, ovarian cancer, and four other cancer types, but not in the remaining 26 cancer types. HRDsum and tumor mutational burden (TMB) correlated significantly positively across cancer types ( ρ = 0.42) and within 18 cancer types. HRDsum and a proliferation metagene correlated significantly positively across cancer types ( ρ = 0.52) and within 20 cancer types. Mismatch repair deficiency and HRD as well as proofreading deficiency showed a high level of exclusivity. High HRD scores were associated with an immunologically activated tumor microenvironment only in a minority of cancer types. Our data favor the combination of genetic markers, complex genomic markers (including HRDsum and TMB), and other molecular markers (including proliferation scores) for a precise and comprehensive read‐out of the tumor biology and an individually tailored treatment.